A new species of Agave from subgenera Littaea (Agavaceae) from The Sierra Madre Oriental, Mexico - Zamudio Ruiz, Sergio; Sanchez Martinez, Emiliano (Instituto de Ecología, A.C., 1995)
Agave tenuifolia sp. nov. from Queretaro and Tamaulipas states, in eastern Mexico, is described and illustrated. It belongs to the series Striatae of subgenus Littaea, and is close to Agave striata Zucc. ssp. striata, from which it differs in its lax rosettes, few, larger and pliant, recurved leaves, and in its loose thin spike with geminate flowers.